Bagaimana Merancah Kelas Berbicara Bahasa Inggris Anak-Anak? - Retno Dwigustini; Arrizqi Ramadhan; Susilawati Susilawati; Nurhasanah Halim; Chelly Banuwaty Morrison (Linguistic, English Education and Art (LEEA) Journal, 2022)
The research objective is to portray how scaffolding strategy is applied in an English-speaking class of young learners. A qualitative approach with a case study design was employed in the present research. Interviews, observation, and document analysis were used to collect the data. The participants involved in this research consisted of an English teacher and 20 junior high school students. The results indicate that the English teacher applies micro-scaffolding strategies, which are realized in the following six activities: 1) stimulating students' participation and engagement; 2) providing explanations; 3) modelling; 4) repetition drills; 5) confirming students' understanding; and 6) giving feedback. Those activities, combined with role-play technique, have been proven to increase students' positive responses, especially concerning learning excitement, speaking skills element enhancement, and students' confidence. The findings signify that scaffolding is a good strategy for young learners' language skills. The present research strongly recommends exploring new scaffolding activities with the infusion of learning platforms both in full remote and hybrid learning as an endeavour to grant much more tremendous help and support for young learners' productive skills. Keywords: English speaking skills, Scaffolding, Teaching Strategy, Young Learners